2021
DOI: 10.1088/1757-899x/1094/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Machine Learning Models to Forecast COVID-19 Relying on Laboratory Outcomes Characteristics in Children

Abstract: An outbreak of the 2019 novel Coronavirus epidemic (COVID-19) has rapidly spread worldwide. The coronavirus (COVID-19) has also spread among children, but it has been less severe than in adults. The characteristics of COVID-19 laboratory findings play a significant role in clinical manifestations, diagnosis, and treatment. Since the numbers of COVID-19 cases increased, it takes more time to interpret the lab outcomes and provide an accurate diagnosis. Little information about the clinical symptoms and epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In their research findings, KNN was identified as the best classifier for assisting people with dementia in adopting assistive technology. Several other studies [36][37][38][39] have also demonstrated that the KNN classification is accurate and efficient. The KNN algorithm is indeed very simple to comprehend as well as develop.…”
Section: Discussionmentioning
confidence: 85%
“…In their research findings, KNN was identified as the best classifier for assisting people with dementia in adopting assistive technology. Several other studies [36][37][38][39] have also demonstrated that the KNN classification is accurate and efficient. The KNN algorithm is indeed very simple to comprehend as well as develop.…”
Section: Discussionmentioning
confidence: 85%